A revised AMS and tephra chronology for the Late Middle to Early Upper Paleolithic occupations of Ortvale Klde, Republic of Georgia. Issue 151 (February 2021) - Cullen, Victoria L.; Smith, Victoria C.; Tushabramishvili, Nicholaz; Mallol, Carolina; Dee, Michael; Wilkinson, Keith N.; Adler, Daniel S.
Abstract: The nature and timing of the shift from the Late Middle Paleolithic (LMP) to the Early Upper Paleolithic (EUP) varied geographically, temporally, and substantively across the Near East and Eurasia; however, the result of this process was the archaeological disappearance of Middle Paleolithic technologies across the length and breadth of their geographic distribution. Ortvale Klde rockshelter (Republic of Georgia) contains the most detailed LMP-EUP archaeological sequence in the Caucasus, an environmentally and topographically diverse region situated between southwest Asia and Europe. Tephrochronological investigations at the site reveal volcanic ash (tephra) from various volcanic sources and provide a tephrostratigraphy for the site that will facilitate future correlations in the region. We correlate one of the cryptotephra layers to the large, caldera-forming Nemrut Formation eruption (30, 000 years ago) from Nemrut volcano in Turkey. We integrate this tephrochronological constraint with new radiocarbon dates and published ages in an OxCal Bayesian age model to produce a revised chronology for the site. This model increases the ages for the end of the LMP (∼47.5–44.2 ka cal BP) and appearance of the EUP (∼46.7–43.6 ka cal BP) at Ortvale Klde, which are earlier than those currently reported for other sites in the Caucasus but similar to estimates for specific sites in southwest Asia and eastern Europe. These data, coupled with archaeological, stratigraphic, and taphonomic observations, suggest that at Ortvale Klde, (1) the appearance of EUP technologies of bone and stone has no technological roots in the preceding LMP, (2) a LMP population vacuum likely preceded the appearance of these EUP technologies, and (3) the systematic combination of tephra correlations and absolute dating chronologies promises to substantially improve our inter-regional understanding of this critical time interval of human evolution and the potential interconnectedness of hominins at different sites.